NUMERICAL ANALYSIS OF CONCRETE-FLY ASH AND CONCRETE-OPC IN MULTI- STOREY BUILDINGS DURING EARTHQUAKES - Nasution, Habibi Azka; Gea, Mitra Lestari; Nasution, Budiman (Universitas Negeri Medan, 2025)
OPC-concrete is the most commonly used type of concrete. The production of OPC produces CO2 emissions, which is one of the main causes of climate change and global warming. A recent innovation used as a high-strength concrete admixture is fly ash. Earthquakes pose a serious threat to the safety and stability of high-rise buildings. This study uses a finite difference method computational approach to analyze the seismic behavior of multi-storey buildings using fly ash concrete and opc concrete by utilizing data on stiffness, mass, damping, and earthquake acceleration. Based on the simulation results, the mode shape graphs of fly ash concrete and opc concrete are similar but the vibration frequencies of both are different, where the frequency of fly ash concrete is higher than the frequency of opc concrete. The displacements of the buildings with fly ash concrete and opc concrete still meet the applicable deviation allowance, where the maximum displacements of the buildings are 0.00308 m and 0.00342 m, respectively, while the maximum shear force of both buildings occurs on the first floor, which is 5967.59 N and 5104.78 N, respectively.